The combined effects of alcohol and marijuana use prior to traumatic brain injury on mortality. (December 2020) - Leskovan, John J.; Patel, Puja D.; Pederson, John; Moore, Aaron; Afaneh, Amer; Brown, Laura R.
Abstract: Background: Alcohol (ETOH) intoxication is a common comorbidity in traumatic brain injury (TBI), and marijuana (THC) has been implicated as a major risk factor for trauma. The objective this study was to investigate the combined effects of ETOH and THC on mortality after TBI. Materials and methods: A retrospective review of patient data was performed to assess adult (>18 years) patients with brain injuries between January 2012 and December 2018. Included patients sustained TBI (Abbreviated Injury Scale (AIS 1-6)) and were divided into two groups: No Substances and THC + ETOH. Results: 1085 (median age 52 years [range: 18–97 years]; 33.5% female (364/1085)) patients met the inclusion criteria. Significant differences for mortality at discharge were found between groups (p = 0.0025) with higher mortality in the No Substances group. On multiple logistic regression, a positive test for both ETOH + THC was found not to independently predict mortality at discharge, while age, Glasgow Coma Scale, intensive care unit stay, Injury Severity Score, length of hospital stay, and days on ventilator were independent predictors. Conclusions: After controlling for confounding variables, positive ETOH + THC screens were not found to be independent predictors of mortality at discharge. Therefore, our results indicated no survival benefit for TBI patients with concomitant ETOH and THC use prior to injury. Highlights: ⁃ No survival benefit of alcohol and marijuana for all traumatic brain injury levels ⁃ Glasgow Coma Scale predicts mortality for all traumatic brain injury levels ⁃ Length of stay predicts mortality for all traumatic brain injury levels